PENGARUH PENGETAHUAN PERPAJAKAN, KUALITAS PELAYANAN PAJAK DAN SANKSI PAJAK TERHADAP MOTIVASI WAJIB PAJAK ORANG PRIBADI DALAM MEMBAYAR PAJAK - Caroko, Bayu (Jurnal Mahasiswa Perpajakan, 2015)
Tax has an important role in state revenue sources, as the country's largest revenue comes from taxes sector. however tax revenue in Indonesia is still not up to look at the number of individual taxpayers. The Tax Office Primary Singosari are growing every year but in terms of the SPT was still a lot of taxpayers who do not deliver the SPT. It was feared because it is not the taxpayer does not fulfill its obligation to calculate and pay the tax due. This study aims to explain the effect of tax knowledge, quality of service tax and tax penalties to motivate taxpayers to pay taxes. Type of research is explanatory research with quantitative approach. The results of simultaneous analysis showed that the variables of knowledge, quality of service and tax penalties affect the motivation of individual taxpayers in paying taxes. while the partial test results or individual taxes demonstrate knowledge, quality of service tax and tax penalties significantly influence the motivation of individual taxpayers in paying taxes. Expected results of the research can be used as a reference for further research to develop this research by adding a variable that has not been addressed in this study. Keywords : STO Singosari, tax of knowledge, quality of tax service, tax punishment, motivation individual taxpayer in paying taxes